The aggregate production function and Solow's "three denials" - Jesus Felipe; John S. L. McCombie (Levy Economics Institute of Bard College, 2024)
This paper offers a retrospective view of the key pillar of Solow's neoclassical growth model, namely the aggregate production function. We review how this tool came to life and how it has survived until today, despite three criticisms that undermined its raison d'être. They are the Cambridge Capital Theory Controversies, the Aggregation Problem, and the Accounting Identity. These criticisms were forgotten by the profession, not because they were wrong but because of the key role played by Robert Solow in the field. Today, these criticisms are not even mentioned when students are introduced to (neoclassical) growth theory, which is presented in most economics departments and macroeconomics textbooks as the only theory worth studying
Keywords: B22; B31; B32; B41; E13; E25; 330; Accounting Identity; Aggregation Problem; Cambridge Capital Theory Controversies; Solow